Effect of Various Parameters on Bio-Synthesis of Copper Nanoparticles Using Citrus Medica Linn (Lemon) Extract and Its Antibacterial Activity - Pradhan, Sharmila; Shrestha, Rajeswori; Bhandari, Khuma (Amrit Research Journal, 2020)
This research is focused on bio-synthesis of Copper nanoparticles (CuNPs) using lemon extract to study the effect of various parameters on synthesis and to explore antibacterial activity. The biomolecules present in lemon extract act as self reducing and stabilizing agent. The synthesis of CuNPs was found to be affected by various parameters like volume of the lemon extract, concentration of the precursor and the temperature etc. Preliminary characterization of formation of nanoparticles were done by color change and UV-visible (UV-vis) spectroscopy. Elemental composition of the prepared sample was determined via Energy Dispersive X-ray (EDX) Spectroscopy. Presence of important functional groups associated with biomolecules is well characterized by Fourier Transform Infrared spectroscopy (FTIR). Scanning Electron Microscopy (SEM ) revealed the formation agglomerated CuNPs of different shape and sizes and the X-ray diffraction pattern showed the formation of purely crystalline nature of CuNPs. Finally, agar well diffusion method showed that CuNPs have potential antibacterial activity against Gram-ve bacteria compared to Gram +ve bacteria.